Teacher's Strategy in Improving Students' Al-Qur'an Reading Ability - Jaafar, Azhar; Irawan, Dedi; Firdaus, Firdaus; Akem, Umar (Al-kayyis: Journal of Islamic Education, 2025)
Learning the Qur'an is the main thing that every Muslim must learn. Because reading the Qur'an is not only reading but must be in accordance with the laws of tajweed which is good and correct. This study aims to evaluate the effectiveness of the methods applied in each stage, identify challenges that arise such as obstacles in muraja'ah or lack of motivation and develop practical recommendations for tahfidz teachers so that the learning process becomes more effective, structured and comprehensive. This research uses a qualitative approach with a descriptive research type. The results of the analysis show that the strategy carried out by the teacher to improve the ability to read the Qur'an is very much needed so that the reading of the Qur'an is in accordance with the law of tajweed and avoid mistakes. Learning the Qur'an with good and correct reading in accordance with the science of tajweed can be achieved with existing methods, The role of Tahfiz teachers in fostering the memorizers of the Qur'an is needed because in order to achieve a good Tahfiz program and produce students who memorize well in terms of tajweed and mad along with the buzz. This strategy is very useful because it helps to improve the reading of the Qur'an and can produce students who are bail and correct in reading the Qur'an.